microRNA-155 deficiency results in decreased macrophage inflammation and attenuated atherogenesis in apoE(−/−) mice - Du, Fen (2014)
OBJECTIVE: microRNA-155 (miR155) plays a critical role in immunity and macrophage inflammation. We aim to investigate the role of miR155 in atherogenesis. APPROACH AND RESULTS: Quantitative real-time PCR showed that miR155 was expressed in mouse and human atherosclerotic lesions. miR155 expression in macrophages was positively correlated with proinflammatory cytokine expression. Lentivirus-mediated overexpression of miR155 in macrophages enhanced their inflammatory response to LPS through targeting SOCS-1, and impaired cholesterol efflux from acetylated LDL-loaded macrophages, whereas deficiency of miR155 blunted macrophage inflammatory responses, and enhanced cholesterol efflux possibly via enhancing lipid loading-induced macrophage autophagy. We next examined the atherogenesis in apoE(−/−) and miR155(−/−)/apoE(−/−) (DKO) mice fed a western diet. Compared with apoE(−/−) mice, the DKO mice developed less atherosclerosis lesion in aortic root, with reduced neutral lipid content and macrophages. Flow cytometric analysis showed that there were increased number of regulatory T cells, and reduced numbers of Th17 cells and CD11b+/Ly6C(high) cells in the spleen of DKO mice. Peritoneal macrophages from the DKO mice had significantly reduced pro-inflammatory cytokine expression and secretion both in the absence and presence of LPS stimulation. To determine whether miR155 in leukocytes contributes to atherosclerosis, we performed bone marrow transplantation study. Deficiency of miR155 in bone marrow-derived cells suppressed atherogenesis in apoE(−/−) mice, demonstrating that hematopoietic cell-derived miR155 plays a critical role. CONCLUSION: miR155 deficiency attenuates atherogenesis in apoE(−/−) mice by reducing inflammatory responses of macrophages, enhancing macrophage cholesterol efflux and resulting in an anti-atherogenic leukocyte profile. Targeting miR155 may be a promising strategy to halt atherogenesis.